Determinação do excesso de mão-de-obra na região de Viçosa, MG, ano agrícola 1967/68 - da Rocha Ferreira, Léo; Palma, Victor; de Azevedo, Roberto; de Oliveira, Antônio Jorge; Batista de Oliveira, Evonir (Revista Ceres, 2025)
Economic development demands structural changes in the agricultural sector. Based on this fact countries with a high rate of population groeth and a large part of the population located in rural areas must search for better, labor efficiency in agricultural activities. Underutilized labor liberated from agriculture can be utilized in other sectors of the economy.